2008
DOI: 10.1593/neo.08330
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Metaplastic and Dysplastic Changes in Mouse Pancreas Induced by Cyclooxygenase-2 Overexpression

Abstract: Cyclooxygenase-2 (COX-2) overexpression is an established factor linking chronic inflammation with metaplastic and neoplastic change in various tissues. We generated transgenic mice (BK5.COX-2) in which elevation of COX-2 and its effectors trigger a metaplasia-dysplasia sequence in exocrine pancreas. Histologic evaluation revealed a chronic pancreatitis-like state characterized by acinar-to-ductal metaplasia and a well-vascularized fibroinflammatory stroma that develops by 3 months. By 6 to 8 months, strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 77 publications
3
72
1
Order By: Relevance
“…Additionally, HCC is known to be an inflammation-related malignancy, which is attributed to the above-mentioned risk factors. Cyclooxygenase-2 (COX-2), a rate-limiting enzyme in the production of prostaglandins, is usually induced by stimuli involved in inflammatory responses and has been shown to be associated with carcinogenesis and tumor progression (4,5). Various HCC-related molecules such as hepatitis B virus X protein (6), hepatitis C virus (7) and diethylinitrosamine (DEN) (8), have been reported to induce the expression of COX-2, which finally facilitates hepatocarcinogenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HCC is known to be an inflammation-related malignancy, which is attributed to the above-mentioned risk factors. Cyclooxygenase-2 (COX-2), a rate-limiting enzyme in the production of prostaglandins, is usually induced by stimuli involved in inflammatory responses and has been shown to be associated with carcinogenesis and tumor progression (4,5). Various HCC-related molecules such as hepatitis B virus X protein (6), hepatitis C virus (7) and diethylinitrosamine (DEN) (8), have been reported to induce the expression of COX-2, which finally facilitates hepatocarcinogenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional NSAIDs can inhibit both COX-1 and COX-2, to varying degrees. Selective inhibition of COX-2 by celecoxib was found to effectively suppress the growth of pancreatic cancer cells in vitro (17) and to inhibit PDAC tumor growth and angiogenesis in orthotopic implantation tumor models (33). More recently it was shown that Celecoxib could slow or prevent the progression of early PanIn lesions in mouse models to metastatic disease (32).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of COX-2 in chronic pancreatitis is primarily localized in the cytoplasm of pancreatic acinar cells, islet cells, and ductal cells (6), while in pancreatic adenocarcinoma it is localized primarily to cancer cells (7). Transgenic over-expression of COX-2 in the pancreas led to the development of pancreatic fibrosis and even cellular transformation (17). However, despite the strong correlation between COX-2 and pancreatic fibrosis, the mechanisms involved in COX-2 mediated effects on the stroma are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic agents like gemcitabine have been approved for pancreatic cancer not amenable to surgery, but have not shown clear therapeutic effects (Lohr and Jesenofsky, 2009). In order to understand the complexities of molecular mechanisms and drug interactions various mouse models have been developed (Lee et al, 1995;Colby et al, 2008;Jung et al, 2011). In the following sections, common cellular pathways in pancreatitis and pancreatic cancer will be considered, and their role in the transformation of acute to chronic disease, and ultimately cancer, will be discussed.…”
Section: Epidemiologymentioning
confidence: 99%
“…COX-2 has been linked to development of pancreatic dysplasia and PDAC and may form a potential link between CP and subsequent development of pancreatic cancer. Elevated COX-2 has been associated with pancreatic cancer cell proliferation (Sun et al, 2009) and tumor growth (Colby et al, 2008;Mukherjee et al, 2009;Hill et al, 2012). Moreover, a recent study has shown that a combination therapy, involving pharmacologic inhibitors of COX-2 and histone deacetylases (HDAC), a family of enzymes that regulate paramount cellular activities, results in a complete inhibition of tumor growth.…”
Section: Cox-2 Overexpressionmentioning
confidence: 99%